The moderating role of complaint handling on brand hate in the cancel culture - Abbasi, A.Z. (Emerald Group Holdings Ltd., 2022)
Purpose: This study investigates the moderating role of complaint handling between ideological incompatibility, symbolic incongruity, negative past experience and corporate social irresponsibility on brand hate. Design/methodology/approach: The study employs the Duplex Hate theory which assumes that hate is the manifestation of multiple factors. A survey-based self-administered questionnaire was used to collect data from 400 smartphone users at Rawalpindi and Islamabad, Pakistan. Findings: The findings suggest that ideological incompatibility, symbolic incongruity, negative past experience and corporate social irresponsibility contributes to brand hate. The complaint handling (moderator) weakens the effects of ideological incompatibility and symbolic incongruity on brand hate. Practical implications: The research provides insights into the cancel culture and clarifies how brand hate can be controlled. Originality/value: Empirical study on the antecedents of brand hate remains insufficient. The current study contributes to the brand hate literature by providing an understanding of the phenomenon of brand hate and by empirically examining the different antecedents responsible for causing the behavior. The study has also provided an additional determinant of brand hate, which is corporate social irresponsibility. The role of moderators for controlling brand hate is greatly ignored in the existing literature. The current work also extends previous studies by investigating a moderating factor for reducing brand hate, which is complaint handling. Â© 2022, Emerald Publishing Limited.